The Palestine War of 1948 in the Swedish pressA historical study - Dr. Kassim mahdi Hamza (Peerian Journals Publishing, 2024)
The illegal immigration of Jews to Palestine was the key to the occupation of Palestine by the Zionists and the displacement of its people. The Judaization of Palestine and making it an arena for the implementation of the plans of the world of Zionism was being coordinated high between the Zionists and the major colonial powers, led by the United States of America, Britain and France, as documented by the press in Sweden. Moreover, what helped to carry out these malicious schemes in Palestine is the existence of the Arab regimes that were falling in the orbit of the Western government. The United Nations, as it was yesterday, is today an international organization controlled by the great Powers of the world, which are governed by their own interests and wishes. It was a false witness to the occupation of the land of Palestine and the displacement of its people. Most newspaper articles in Sweden have sympathized with the entity of the occupation with such weak arguments, including the false freedom and democracy enjoyed by that entity, forgetting its illegitimate birth. Lastly, While Arab preparations for the war are waning, Israel's image shines and gives the image of the custodial lamb.
Keywords: The 1948 war; Swedish press